From Speaking to Acting - Enhancing Interactivities of Learning in the 3D Virtual Worlds (International Conference on Computers in Education, 2011)
Some common educational activities being discussed for fitting 3D virtual worlds include the following types: interpersonal role-play, oral production, and traditional lecturing [1]. These examples are discussion-based or dialogue-oriented by heavily use of the text-typing or voice communication tools in the virtual scenarios. To take more advantages of the virtual space for enhancing the learning interactivity, this paper demonstrates an example which addresses the interactivities not only among learners by texting but also between learners and learning context. Through configuring the Activity Awareness (AA) model [2] with our designed learning context and activities for teamwork in computer-supported collaborations, we attempt to explore the possibility of enhancing interactivities in the virtual worlds, e.g., a learning task requiring learners to manipulate 3D virtual objects collaboratively. Rather than using commercial platforms like the Second Life, we develop a lightweight yet dedicated system to implement the experiment. Our study demonstrates that the AA model is more feasible for enhancing the interactivity among learners in the learning environment than discussion-based activity is in the 3D virtual learning worlds.